2020
DOI: 10.1371/journal.pone.0234819
|View full text |Cite
|
Sign up to set email alerts
|

Does frequency of supportive supervisory visits influence health service delivery?—Dose and response study

Abstract: High quality care-at a minimum-is a combination of the availability of tangible resources as well as a capable and motivated health workforce. Researchers have suggested that supportive supervision can increase both the performance and motivation of health workers and the quality of care. This study is aimed at assessing the required number of visits and time between visits to bring about improvements in health service delivery. The study employed a primary health care performance improvement conceptual framew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…This is substantiated by a recent study that assesses the frequency of supportive supervision and its dose-response relationship. The study found that an optimum number of regular supportive supervision has an incremental effect on service delivery improvements (29).…”
Section: Discussionmentioning
confidence: 91%
“…This is substantiated by a recent study that assesses the frequency of supportive supervision and its dose-response relationship. The study found that an optimum number of regular supportive supervision has an incremental effect on service delivery improvements (29).…”
Section: Discussionmentioning
confidence: 91%
“…The existence of periodic supervision activities tends to maintain service quality in high standard, with the ability to pay attention to service users' characteristics. [13][14][15][16] Superiors or supervisors act as part of the first level of management in charge of controlling performance as well as the quality of health service. [17][18][19] In this study, knowledge significantly affects the quality of medical records.…”
Section: Resultsmentioning
confidence: 99%
“…This is substantiated by a recent study that assessed the frequency of supportive supervision and its dose-response relationship. The study found that an optimum number of regular supportive supervision has an incremental effect on service delivery improvements [ 22 ].…”
Section: Discussionmentioning
confidence: 99%